2004
DOI: 10.1136/thx.2003.000893
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of bleomycin induced lung fibrosis by candesartan cilexetil, an angiotensin II type 1 receptor antagonist

Abstract: Background: Signalling of angiotensin II via angiotensin II type 1 receptor (AT1) promotes cardiac and renal fibrosis, but its role in lung fibrosis is little understood. Using a rat bleomycin (BLM) induced model of pulmonary fibrosis, we examined the expression of AT1 in the lung and the effect of an AT1 antagonist on pulmonary fibrosis. Methods: Adult male Sprague-Dawley rats were given 0.3 mg/kg BLM intratracheally. Two days earlier they had received 10 mg/kg/day of the AT1 antagonist candesartan cilexetil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(113 citation statements)
references
References 34 publications
8
101
2
2
Order By: Relevance
“…Up-regulation in AT1 receptor expression occurred in lung parenchyma after bleomycin-induced lung injury. These studies' results suggest that angiotensinogen and AT1 receptors are expressed in lung tissue (7,8,17). Previous assessments have also shown that AT1 receptor antagonists decrease lung collagen deposition, which was confirmed in our observations (7,17,20).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Up-regulation in AT1 receptor expression occurred in lung parenchyma after bleomycin-induced lung injury. These studies' results suggest that angiotensinogen and AT1 receptors are expressed in lung tissue (7,8,17). Previous assessments have also shown that AT1 receptor antagonists decrease lung collagen deposition, which was confirmed in our observations (7,17,20).…”
Section: Discussionsupporting
confidence: 80%
“…The present study showed that valsartan significantly decreased lung inflammatory infiltration after bleomycin exposure. Several studies have reported an anti-inflammatory effect of AT1 receptor blockade (17)(18)(19). An enhancement in lung hydroxyproline content (as a remarkable indicator of collagen quantity) was observed on the 21st day of treatment after bleomycin exposure in the bleomycin group.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…), Angiotensin converting enzyme inhibitors (Captopril (R. Wang, Ibarra-Sunga, Verlinski, Pick, & Uhal, 2000), Ramipril (Marshall et al, 2004) etc. ), Angiotensin receptor blockers (Losartan (Fang, Zhu, Hu, & Liu, 2002;Marshall et al, 2004;Yao, Zhu, Zhao, & Lu, 2006), Candesartan (Otsuka, Takahashi, Shiratori, Chiba, & Abe, 2004), Valsartan (F. Liu, Xu, & Ye, 2005;Mancini & Khalil, 2005) etc. ), Anticoagulants (TFPI = tissue factor pathway inhibitor (Kijiyama et al, 2006), Urokinase (Hart, Whidden, Green, Henkin, & Woods, 1994;Hattori et al, 2004;Howell et al, 2001;Howell, Laurent, & Chambers, 2002;Ikeda, Hirose, Koto, Hirano, & Shigematsu, 1989), Heparin (Gunther et al, 2003;Piguet, Van, & Guo, 1996), APC = anticoagulant protein C (S. Shimizu et al, 2003;H.…”
Section: Drug Intervention Studies In the Bleomycin Modelmentioning
confidence: 99%
“…The prototype ACE inhibitors captopril or lisinopril attenuated experimental lung fibrosis induced by monocrotaline, 51 bleomycin 52 or paraquat; 53 the ACE inhibitors also were found to be potent inhibitors of bleomycin-or TNF-a-induced apoptosis of lung epithelial cells. 54,55 The ANG receptor AT1 antagonists losartan or candesartan have been shown to prevent lung fibrosis in response to radiation 56 or bleomycin, 57,58 and also blocked apoptosis of lung alveolar epithelial cells in response to bleomycin 57 or the antiarrhythmic agent amiodarone. 59 Given the central role of epithelial cells death in lung injury in a variety of disease states, attention as been focused on defining the role of ANGII in apoptosis of lung alveolar epithelials (AECs).…”
Section: The Endocrine Ras Versus Local Tissue Rasesmentioning
confidence: 99%